2020
DOI: 10.3390/metabo10020056
|View full text |Cite
|
Sign up to set email alerts
|

Self-Redirection of Metabolic Flux toward Squalene and Ethanol Pathways by Engineered Yeast

Abstract: We have previously reported that squalene overproducing yeast self-downregulate the expression of the ethanol pathway (non-essential pathway) to divert the metabolic flux to the squalene pathway. In this study, the effect of co-production of squalene and ethanol on other non-essential pathways (fusel alcohol pathway, FA) of Saccharomyces cerevisiae was evaluated. However, before that, 13 constitutive promoters, like IRA1p, PET9p, RHO1p, CMD1p, ATP16p, USA3p, RER2p, COQ1p, RIM1p, GRS1p, MAK5p, and BRN1p, were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Later, two iron and copper repressible promoters P AFT1 and P CTR1 , respectively are characterized and used to repress the ERG1 gene in S. cerevisiae towards squalene bioproduction. ERG1 repression with metal ion repressible P CTR1 promoter has enhanced squalene up to twofold when compared to P AFT1 promoter (Manzoor et al 2020). In the same study, TFBS TEF1 and TFBS HHF2 were engineered into different constitutive promoters thereby enhancing the strength of the yeast constitutive promoters.…”
Section: Promoter Based Engineering Strategies Towards Squalene Synth...mentioning
confidence: 96%
See 2 more Smart Citations
“…Later, two iron and copper repressible promoters P AFT1 and P CTR1 , respectively are characterized and used to repress the ERG1 gene in S. cerevisiae towards squalene bioproduction. ERG1 repression with metal ion repressible P CTR1 promoter has enhanced squalene up to twofold when compared to P AFT1 promoter (Manzoor et al 2020). In the same study, TFBS TEF1 and TFBS HHF2 were engineered into different constitutive promoters thereby enhancing the strength of the yeast constitutive promoters.…”
Section: Promoter Based Engineering Strategies Towards Squalene Synth...mentioning
confidence: 96%
“…ERG1 gene codes for squalene monooxygenase in the MVA pathway downstream of squalene in S. cerevisiae. Being an essential gene, disruption of ERG1 leads to a lethal phenotype and therefore repression of ERG1 gene by promoter replacement has become a prominent strategy in the development of cell factories towards squalene biosynthesis (Hull et al 2014;Manzoor et al 2020;Liu et al 2020a, b;Zhu et al 2021). Also, the usage of repressible promoters provides better economic feasibility when compared to the enzyme inhibitors at an industrial level.…”
Section: Promoter Based Engineering Strategies Towards Squalene Synth...mentioning
confidence: 99%
See 1 more Smart Citation
“…The coaccumulation and co-occurrence of terpenoids in LDs provide an opportunity to achieve the high-yield production and storage of terpenoids in LDs. Through the overexpression of diacylglycerol acyltransferase ( DGA1 ) to stimulate the biogenesis of lipid droplets and inhibition of ERG1 expression by employing AFT1p and CTR1p repressible promoters, the squalene titer reached 255.11 mg/L, which was 73.49 times that of the wild-type strain. , Another study showed that the overexpression of DGA1 in the engineered strain of S. cerevisiae with the overexpression of tHMGR can enhance the lipid bodies biosynthesis, leading to 12-fold increase in the squalene production compared with the original strain . These results provided a feasible scheme for the further efficient synthesis of hydrophobic compounds in S. cerevisiae .…”
Section: Regulation Strategy For Efficient Biosynthesis Of Squalenementioning
confidence: 99%